Financial Statement Quality and Debt Contracting: Evidence from a Survey of Commercial Lenders - Donelson, Dain C.; Jennings, Ross; Mcinnis, John (Contemporary Accounting Research, 2017)
Abstract We survey commercial bank lenders to better understand how they evaluate and react to variation in financial statement quality and how they view recent changes in accounting standards. A unique aspect of this study is that our respondents focus on medium‐size loans to private companies. In fact, more than 90 percent of the survey respondents primarily make credit decisions on loans between $250 thousand and $50 million. This is in contrast to prior archival research, which focuses primarily on very large loans to public firms or very small loans to private firms. We find that lenders in our sample distinguish among financial statements in terms of quality, including conservatism, primarily on the basis of accrual patterns and restatements. While this general result holds throughout our sample, financial statement quality is substantially more important for lenders making larger loans (over $10 million) as compared to very small loans (under $1 million). In addition, bank lenders are much more likely to respond to low‐quality reporting with collateral and guarantee requirements than with an increase in the interest rate charged. This finding is consistent for lenders making both larger and smaller loans. Finally, despite concerns in the academic literature, bank lenders in our sample actually hold a neutral‐to‐positive view of recent changes in accounting standards. In addition, most do not support current efforts to exempt private companies from some accounting standards.